2013
DOI: 10.1182/blood-2012-12-475566
|View full text |Cite
|
Sign up to set email alerts
|

The Thr224Asn mutation in the VPS45 gene is associated with the congenital neutropenia and primary myelofibrosis of infancy

Abstract: Key Points VPS45 is a new gene associated with severe infections and bone marrow failure in infancy that can be treated by bone marrow transplantation. The mutation affects intracellular storage and transport and results in increased programmed cell death in neutrophils and bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 30 publications
3
89
0
1
Order By: Relevance
“…A growing list of monogenic mutations have been identified: the mitochondrial protein Hax-1, the transcription factor Gfi-1 (4), the cytoskeletal protein Wiskott-Aldrich syndrome protein (5), the enzyme glucose-6-phosphatase, subunit 3 (G6PC3) (6), and the granulocyte colony-stimulating factor (GCSF) receptor (7). Other causes of moderate to severe inherited neutropenias are mutations in the phospholipase transacylase tafazzin in Barth syndrome (8), lysosomal trafficking regulator in Chediak-Higashi syndrome (9), the clathrin-associated AP3B1 in type 2 Hermansky-Pudlak syndrome (10), the endosomal protein p14 (11), the serine/threonine kinase STK4 (12), the sorting protein Vps45 (13,14), the chemokine receptor CXCR4 in WHIM (warts, hypogammaglobulinemia, infections, and myelokathexis) syndrome (15), the ribosomeassociated protein Shwachman-Bodian-Diamond syndrome (SBDS) in SDS (16), and the transcription factor GATA2 in MonoMAC syndrome (17). All of these widely variant genetic disorders appear to result in enhanced or accelerated apoptosis of granulocyte precursors, such as the promyelocyte.…”
Section: Review Glaubach Et Almentioning
confidence: 99%
“…A growing list of monogenic mutations have been identified: the mitochondrial protein Hax-1, the transcription factor Gfi-1 (4), the cytoskeletal protein Wiskott-Aldrich syndrome protein (5), the enzyme glucose-6-phosphatase, subunit 3 (G6PC3) (6), and the granulocyte colony-stimulating factor (GCSF) receptor (7). Other causes of moderate to severe inherited neutropenias are mutations in the phospholipase transacylase tafazzin in Barth syndrome (8), lysosomal trafficking regulator in Chediak-Higashi syndrome (9), the clathrin-associated AP3B1 in type 2 Hermansky-Pudlak syndrome (10), the endosomal protein p14 (11), the serine/threonine kinase STK4 (12), the sorting protein Vps45 (13,14), the chemokine receptor CXCR4 in WHIM (warts, hypogammaglobulinemia, infections, and myelokathexis) syndrome (15), the ribosomeassociated protein Shwachman-Bodian-Diamond syndrome (SBDS) in SDS (16), and the transcription factor GATA2 in MonoMAC syndrome (17). All of these widely variant genetic disorders appear to result in enhanced or accelerated apoptosis of granulocyte precursors, such as the promyelocyte.…”
Section: Review Glaubach Et Almentioning
confidence: 99%
“…Although the exact pathomechanism is unknown, vacuolar sorting proteins are involved in endosomal trafficking and protein recycling in the trans-Golgi network. Indicating their importance in granulocyte development, another VPS protein, VPS45 was recently found to be mutated in severe congenital neutropenia patients [98, 99]. In accordance with other severe congenital neutropenias, VPS45 mutant patients had severe infections and their neutrophils and bone marrow myeloid cells showed accelerated apoptosis.…”
Section: Defects Of Vesicular Transportmentioning
confidence: 96%
“…Interestingly, fibroblasts from affected patients lacked lysosomes, suggesting a role for VPS45 in biogenesis of the endosomal-lysosomal pathway. 40 This adds VPS45 to the growing list of lysosomal-related proteins associated with congenital neutropenia, including those associated with Chediak-Higashi syndrome, Hermansky-Pudlak syndrome type 2, Griscelli syndrome, Cohen syndrome, and variants in the endosomal adaptor protein p14 associated with primary immunodeficiency.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…Five infants with neutropenia, recurrent and severe infections, defective platelet aggregation, myelofibrosis, and progressive bone marrow failure were studied by homozygosity mapping and WES. 40 Independently, another group examined 7 patients with similar phenotypes in 5 families by linkage mapping and WES. 41 These studies revealed missense mutations in VPS45, which encodes a protein that participates in trafficking in the endosomal pathway.…”
Section: Disease Diagnosismentioning
confidence: 99%